The Effect Of Adding Silver Nanoparticles In Tin Surface Finish Electroplated With Ultrasonication On Wettability And Strength Of SAC305 Solder Joint - Tneh, Kin Man (Universiti Sains Malaysia, 2022)
The development of electronic packaging has introduced various types of surface finish on copper substrate to improve bonding performance of solder. This affects the soldering and the intermetallic compound that formed at the solder/substrate interface which eventually influence the reliability of solder joint. The purpose of this study is to develop nanocomposite coating by co-depositing Ag nanoparticles into Sn via ultrasonic-assisted electroplating technique with ultrasonication. Sn coating and Sn/AgNPs coating were prepared using electroplating process with incorporation of 0W, 10W, 20W, 40W, 60W, and 80W ultrasonication. Phase analysis via X-ray diffraction was done to assess phases in the coating, and thickness of coating was measured via scanning electron microscope. Coatings were later analysed for surface roughness via atomic force microscope, before proceeded to reflow of commercial SAC305 solder at 250oC for 150 seconds. Wetting angle of solder reflowed on coated substrate was measured and single-lap joint shear test was done to assess strength of solder joint. The results demonstrated that coating electroplated with ultrasonication of 40W exhibited the lowest surface roughness (4.07μm and 13.44μm) and the thickest coating layer (6.61μm and 11.3μm) for Sn coating and Sn/AgNPs coating respectively. Sn/AgNPs coating exhibited higher surface roughness and thicker coating layer compared with Sn coating. The lowest surface roughness obtained by coatings with 40W ultrasonication exhibited the best wettability with the lowest contact angle (20o-22o). The addition of Ag nanoparticles in Sn coating resulted in thicker IMCs layer of solder joint (4.33μm-5.95μm), but significantly reduced the contact angle by mitigating surface tension of bulk solder and improved the shear strength of SAC305 solder alloy due to lower contact angle.